2022
DOI: 10.3389/fendo.2022.877341
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cardiac Complications in Patients With Pheochromocytoma and Paraganglioma: A Retrospective Single-Center Study

Abstract: BackgroundCatecholamine excess arising from pheochromocytomas and paragangliomas (PPGLs) can cause a wide spectrum of cardiac manifestations. Although there are reviews of reported cases, these reviews lack detailed data, which makes it impossible to perform an accurate analysis. In this study, we conducted a comprehensive analysis of cardiovascular complications (CCs), including PPGL-related myocardial injury, cardiogenic shock, and arrhythmias requiring antiarrhythmic therapy, in a large cohort of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…The vast majority of published case reports of catecholamine and takotsubolike CMP are associated mainly with an overproduction of adrenaline or both adrenaline and noradrenaline, that is, corresponding to an adrenergic phenotype. 11,13,26 Our work shows that it is predominantly the adrenergic phenotype that shows clinical and laboratory changes with normal coronary angiographic findings categorized as type 2 MI and takotsubo-like CMP. In our cohort, only 2 patients with takotsubo-like CMP showed a noradrenergic phenotype due to the less frequent but possible massive sudden release of noradrenaline.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The vast majority of published case reports of catecholamine and takotsubolike CMP are associated mainly with an overproduction of adrenaline or both adrenaline and noradrenaline, that is, corresponding to an adrenergic phenotype. 11,13,26 Our work shows that it is predominantly the adrenergic phenotype that shows clinical and laboratory changes with normal coronary angiographic findings categorized as type 2 MI and takotsubo-like CMP. In our cohort, only 2 patients with takotsubo-like CMP showed a noradrenergic phenotype due to the less frequent but possible massive sudden release of noradrenaline.…”
Section: Discussionmentioning
confidence: 76%
“…Zhao et al 26 found a higher frequency of complications in women with PPGL than in men in a similar group of patients. 26 However, our work shows no sex differences in the incidence of cardiovascular complications in PPGL.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…46 Platelet activation and aggregation are critically involved in the pathophysiology of various diseases such as hypertension, diabetes, and cardiac diseases. 47,48 MetS increases the difficulty of managing psoriatic patients with coronary artery diseases, and because of the increased risk of cardiovascular events associated with these conditions, it is vital to detect, prevent, and treat them as early as possible. Dermatologists are often the first to patients, and they need to identify MetS early and manage it.…”
Section: Discussionmentioning
confidence: 99%